Chasing for information during the COVID-19 panic: The role of Google search on global stock market - Chaiyuth Padungsaksawasdi; Sirimon Treepongkaruna (Cogent Economics & Finance, 2021)
This paper examines the causal relationship between global stock market performance and Google search volume index (SVI) surrounding the disastrous event of the coronavirus (COVID-19) outbreak. Based on 6,106 stock index-day observations of 71 countries during the period from 1 January 2020 to 29 May 2020, we find that both the SVI and the growth in confirmed cases lower the global stock market returns. Consistent with the information discovery theory, we find when the confirmed cases increase, retail investors search for more information, improving their returns on stock indices during the outbreak. Finally, our further instrumental-variable analysis shows that our results are unlikely confounded by endogeneity.
Keywords: 330; Behavioral finance; COVID-19; Google Search volume index; Investor attention; Stock market performance